2012
DOI: 10.1007/s10964-012-9826-z
|View full text |Cite
|
Sign up to set email alerts
|

Change in Parent- and Child-Reported Internalizing and Externalizing Behaviors Among Substance Abusing Runaways: The Effects of Family and Individual Treatments

Abstract: Shelter-recruited adolescents are known to have high rates of substance abuse and co-occurring internalizing and externalizing problem behaviors. Many studies have documented these mental health concerns, but only a small number of studies have tested interventions that may be useful for ameliorating these vulnerabilities. The current study compared three empirically supported psychotherapy interventions, Motivational Interviewing (MI), the Community Reinforcement Approach (CRA), and Ecologically-Based Family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Penney and Skilling (2012) found that caregiver's reports of internalizing behaviors were not correlated with clinical diagnoses of mood or depressive disorders. In addition, while there are some evidence-based interventions for mood and anxiety disorders among children (Slesnick, Guo, & Feng, 2013;Tompson, McNeil, Rea & Asarnow, 2000;Uliaszek, Wilson, Mayberry, Cox, & Maslar, 2014), the majority of research regarding evidence-based psychotherapies for children and adolescents focus on externalizing behaviors such as attention-deficit hyperactivity disorder and conduct disorder (Weisz & Kazdin, 2010). This may be because externalizing behaviors "demand" more attention.…”
Section: Implications For Practice Research and Policymentioning
confidence: 99%
“…Penney and Skilling (2012) found that caregiver's reports of internalizing behaviors were not correlated with clinical diagnoses of mood or depressive disorders. In addition, while there are some evidence-based interventions for mood and anxiety disorders among children (Slesnick, Guo, & Feng, 2013;Tompson, McNeil, Rea & Asarnow, 2000;Uliaszek, Wilson, Mayberry, Cox, & Maslar, 2014), the majority of research regarding evidence-based psychotherapies for children and adolescents focus on externalizing behaviors such as attention-deficit hyperactivity disorder and conduct disorder (Weisz & Kazdin, 2010). This may be because externalizing behaviors "demand" more attention.…”
Section: Implications For Practice Research and Policymentioning
confidence: 99%
“…This review identified several studies which compared the effectiveness of family therapy with other interventions for various child and youth mental health diagnoses (Garoff et al, 2012;Horigian et al, 2013;Slesnick, Guo, & Feng, 2013;Trowell et al, 2007). Although the focus of this review is family therapy only, it is important to know how family therapy compares to other interventions in order to ensure ongoing evidence-based practice.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, this study relied on self-report measures that may involve some level of response bias. However, some studies have shown that mothers are relatively good at estimating their children’s behavior problems (Phares, 1997), and parent and child reports are generally similar to each other (Slesnick, Guo, & Feng, 2013). Even so, observational data and teacher reports of child behaviors, for example, could strengthen confidence in the conclusions.…”
Section: Discussionmentioning
confidence: 99%